IDENTIFIKASI TIGA JENIS BUNGA IRIS MENGGUNAKAN ANFIS - Abdul Kadir (Jurnal Teknologi, Fakultas Teknologi Industri, Universitas AKPRIND Indonesia, 2010)
This paper was based on our research in preparing several tools for identification on various houseplants. One of tools we investigated was ANFIS. As a preliminary research, we tried to apply ANFIS to identify three kinds of Iris. As we know, many researches have used Iris data came from Fisher’s research in 1936 for classification purposes. In this research, we try to several kinds of parameters of fuzzy logic on input, especially on membership functions and number of function’s membership. The result showed that the worst performance by using bell function was 70%. Not so good. Therefore, many explorations must be conducted to get better performance.